Mortality and long-term dialysis requirement among elderly continuous renal replacement therapy patients in a tertiary referral intensive care unit. (May 2019) - Conroy, Michael; O'Flynn, John; Marsh, Brian
Background: Elderly patients are frequently considered poor candidates for continuous renal replacement therapy in intensive care units, but with little evidence base. Methods: We gathered data regarding patients requiring continuous renal replacement therapy at our institution's intensive care unit during 2012–2014, and compared outcomes between patients of 75 years or older, and younger patients. Results: Older patients had similar intensive care unit mortality to younger patients (41.5% vs. 36.1%, p  = 0.21), but higher hospital mortality (54.2% vs. 44.0%, p  = 0.02), and one-year mortality (63.6% vs. 50.6%, p  = 0.005). There were no significant differences in dialysis-dependence rates between older and younger patients at intensive care unit discharge (31.9% vs. 35.8%, p  = 0.50), and hospital discharge (18.5% vs. 24.2%, 0.32). Rates of new dialysis-dependence between older and younger patients at time of hospital discharge were similar (10.2% vs. 6.0%, p  = 0.20). Conclusions: Intensivists should not withhold continuous renal replacement therapy based on age alone. Other factors should be considered in triage of patients for intensive care unit and continuous renal replacement therapy.